Interplay between alcohol, smoking and HLA genes in RA aetiology - Anna Karin Hedström; Lars Klareskog; Lars Alfredsson; Ola Hössjer (RMD Open)
Objectives The relationship between alcohol consumption and risk for rheumatoid arthritis (RA) is incompletely understood. We aimed to determine the influence of alcohol on anticitrullinated protein antibody (ACPA) positive and ACPA-negative RA and investigate potential interactions between alcohol consumption, smoking and the presence of human leucocyte antigen (HLA)-DRB1-shared epitope (SE).Methods A Swedish population-based case–control study with incident cases of RA was used (3353 cases, 2836 matched controls). Subjects with different HLA-DRB1-SE status, smoking and alcohol consumption were compared regarding risk of ACPA-positive and ACPA-negative RA, by calculating OR with 95% CI employing logistic regression. Interaction on the additive scale between alcohol, HLA-DRB1-SE and smoking was estimated by calculating the attributable proportion (AP) due to interaction.Results Compared with non-drinking, low and moderate alcohol consumption was dose dependently associated with a reduced risk of ACPA-positive and ACPA-negative RA. Independent of smoking habits, non-drinking and the presence of HLA-DRB1-SE interacted to increase the risk of ACPA-positive RA. Among HLA-DRB1-SE positive subjects, there was also a significant interaction between non-drinking and smoking with regard to risk for ACPA-positive RA. A three-way interaction was observed between alcohol, smoking and HLA-DRB1-SE with regard to risk for ACPA-positive RA (AP 0.7, 95% CI 0.6 to 0.8) that remained significant when the influence from the two-way interactions was removed (AP 0.4, 95% CI 0.2 to 0.6).Conclusions Our findings emphasize the need to investigate complex interactions between several environmental and genetic factors in order to better understand the etiology of RA. Whereas of great interest in an aetiological perspective, the finding of a protective role of alcohol on risk for RA must, however, be interpreted with caution in a clinical and public health perspective.